Iterative QR Decomposition-Based Parallel Diversity Noncoherent Detection Algorithm - Wang, Jieling; Zhou, Bin; Zhao, Mao (Wireless personal communications, 2023)
Non-orthogonal multipulse modulation (NMM) has been proven to be with high efficiency in supplying diversity compared with conventional direct sequence spreading system, and the multiuser system constructed by NMM is capable of exploiting both capacity and diversity. However, as conventional code division multiplexing access (CDMA) systems, multi-access interference (MAI) also appears in the NMM-directed multiuser systems, so to improve the system performance, MAI has to be mitigated. Aiming at the MAI in the NMM multiuser systems, QR decomposition-based noncoherent multiuser receiver has been regarded as an effective method for the non-orthogonal multipulse modulation systems. Based on that, we in this paper put forward an iterative decision feedback scheme to pursue the diversity, where two different kinds of interference cancellation algorithms are put forward alternately according to the upper and lower triangular matrices obtained by QR decompositions, respectively. To optimize the detecting property, the criterion of Maximum Rule and the Average Rule are demonstrated and compared by numerical simulations. Finally, a parallel implementation structure is further proposed, which can reduce half of the processing delay for the overall algorithm, meanwhile, the approximate spectral efficiency of the proposed algorithm is presented. Computer simulations are employed to testify the proposed schemes, and the results show that the SNR gains of 1 dB and 2 dB can be obtained by our iterative decision feedback schemes with Maximum Rule and Average Rule , respectively.